2016
DOI: 10.1093/eurheartj/suw034
|View full text |Cite
|
Sign up to set email alerts
|

Switching between ticagrelor and clopidogrel in patients who underwent percutaneous coronary intervention: insight into contemporary practice in Chinese patients

Abstract: Ticagrelor has been proved to be more effective than clopidogrel; however, little is known about the switching between ticagrelor and clopidogrel in real-world clinical practice. We assessed the prevalence, related factors, dose bridging, compliance, and short-term outcomes of in-hospital switching between ticagrelor and clopidogrel in consecutively recruited patients treated by ticagrelor after percutaneous coronary intervention (PCI). A total of 417 eligible patients administrated with ticagrelor in-hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
1
22
1
2
Order By: Relevance
“…Previous studies showed that the rate of nonloading dose was low in patients switching from ticagrelor to clopidogrel . Our study also showed that more than half of the patients (55.3%) with STEMI switched to clopidogrel without loading dose.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Previous studies showed that the rate of nonloading dose was low in patients switching from ticagrelor to clopidogrel . Our study also showed that more than half of the patients (55.3%) with STEMI switched to clopidogrel without loading dose.…”
Section: Discussionsupporting
confidence: 72%
“…In China, switching from ticagrelor to clopidogrel, which is defined as de‐escalation, after PCI is more common. Financial burden, unavailability, and concerns about increased risk of bleeding with ticagrelor are the most important reasons for de‐escalation . In China, most of the patients with ACS who switched from ticagrelor to clopidogrel did not use loading dose .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Большинство этих исследований не показали увели-чения ишемических событий или кровотечений у пациен-тов после «переключения» с прасугрела или тикагрелора на клопидогрел [23,24], однако по результатам анализа регистра SCOPE исследователи сообщали о возможном увеличении риска возникновения кардиоваскулярных событий (ишемических событий + кровотечений) (Отно-шение шансов (ОШ) 5,3; 95% доверительный интервал (ДИ) 2,1-18,2, p = 0,04), преимущественно за счет повы-шения частоты ИМ при краткосрочном наблюдении (42 дня после выписки из стационара) в группе с переключе-нием на клопидогрел [25].…”
unclassified